Effectiveness of learning videos on students' understanding of mathematical concepts - Wulandari, Septiana; Hidajat, Djatmiko; Exacta, Annisa Prima (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This study was conducted to address the issue of students' low comprehension of mathematical concepts. Learning videos were explored as a potential instructional medium to improve this comprehension. The purpose of the research was to examine the effectiveness of learning videos on the comprehension of mathematical concepts among grade XI students at SMA Negeri 3 Sukoharjo. A quantitative research method was employed using a true experimental design with a pretest-posttest control group. The sample consisted of 66 students from classes XI F.5A and XI F.5B, selected through a cluster random sampling technique. Data were collected through a test assessing students' comprehension of mathematical concepts. Prerequisite tests, including normality and homogeneity tests, were conducted prior to hypothesis testing, which was carried out using the t-test. The results indicated that learning videos effectively improved students' comprehension of mathematical concepts. This conclusion was supported by the t-test results, where tcount (2.1085) exceeded ttable (1.669), leading to the rejection of H0 and acceptance of H1​. Furthermore, the experimental group showed a significant increase in average scores after the intervention with learning videos, with the pretest average of 76.24 rising to a posttest average of 87.91. Based on these findings, it can be concluded that learning videos are an effective instructional medium for enhancing the comprehension of mathematical concepts among grade XI students at SMA Negeri 3 Sukoharjo in the 2023/2024 academic year.